Process improvement in the production of oleyl oleate, a liquid wax ester in stirred tank reactor - Basri, M; Radzi, SM; Salleh, A; Ariff, A; Mohamad, R; Rahman, MBA; Rahman, RNZRA (Elsevier Science Bv, 2024)
Indexed by WOS